2003
DOI: 10.1354/vp.40-3-268
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of Canine Cutaneous Mast Cell Tumors

Abstract: Abstract. Twenty-four canine cutaneous nodules, diagnosed as mast cell tumors by fine-needle aspiration biopsy and confirmed by histopathologic analysis by staining with hematoxylin and eosin (HE) and toluidine blue, were analyzed by computerized nuclear morphometry on panoptic-and HE-stained cytopathology slides. Two hundred nuclei per lesion were examined. The morphometric parameters investigated were nuclear area, mean diameter, perimeter, regularity factor, and ellipticity factor. Lesions were graded as I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
2
30

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 24 publications
(76 reference statements)
6
81
2
30
Order By: Relevance
“…5,9,11,13 In the present study, the cytopathologic morphometric data indicated a correlation between MNA and patient survival; Kaplan-Meier analysis demonstrated that survival times were significantly shorter as nuclear area increased. These results corroborate previous data that demonstrate a relationship between morphometric analysis and histopathologic grading 22,34 and confirm the usefulness of cytomorphometry alone as a predictor of survival. Despite a low number of patients, the dogs in the present study were followed clinically for an extended period of time (average of 675 days and maximum of 2,334 days).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5,9,11,13 In the present study, the cytopathologic morphometric data indicated a correlation between MNA and patient survival; Kaplan-Meier analysis demonstrated that survival times were significantly shorter as nuclear area increased. These results corroborate previous data that demonstrate a relationship between morphometric analysis and histopathologic grading 22,34 and confirm the usefulness of cytomorphometry alone as a predictor of survival. Despite a low number of patients, the dogs in the present study were followed clinically for an extended period of time (average of 675 days and maximum of 2,334 days).…”
Section: Discussionsupporting
confidence: 91%
“…7,22,23,34 To reduce subjectivity and increase reproducibility in grading MCTs, some researchers have studied tumor characteristics of potential interest morphometrically, such as nuclear dimension and shape, as well as lesion depth. A previous study 34 found cytopathologic differences in the nuclear sizes of neoplastic mast cells among histopathologic grades of malignancy. Those differences have been confirmed in histologic sections.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the histologic features of these neoplasms were similar to those of fibrosarcoma or leiomyosarcoma. Moreover, the histologic features of the present neoplasms were unlike those of MCTs in other rodent species (e.g., laboratory rats 1 and mice 3,7,9 ) or of poorly differentiated MCTs in canids (grade III) 18 and other animal species. 15,23 With regard to the spindle-shaped tumor cells, the following points should be considered: 1) normal dermal mast cells of Richardson's ground squirrels are pleomorphic and round to spindle, and 2) the present neoplasms may be poorly differentiated and the cells assume a more pleomorphic spindloid appearance.…”
contrasting
confidence: 52%
“…Immune reactivity to p53 tumour suppressor-protein was not found to be associated with prognosis (36,47). Morphometric studies learned that values of nuclear area, mean diameter and perimeter increase with histologic grade (22).…”
Section: F Other Factorsmentioning
confidence: 98%